2017
DOI: 10.1186/s12891-017-1620-3
|View full text |Cite
|
Sign up to set email alerts
|

Progression of function and pain relief as indicators for returning to sports after arthroscopic isolated type II SLAP repair—a prospective study

Abstract: BackgroundOne of the currently used surgical techniques in isolated type II SLAP lesions is arthroscopic SLAP repair. Postoperatively, patients tend to suffer from a prolonged period of pain and are restricted in their sports activities for at least 6 months. The aim of this study was to prospectively evaluate the clinical outcome as well as the postoperative course of pain after arthroscopic type II SLAP repair.MethodsOutcome measures were assessed using the Individual Relative Constant Score (CSindiv), the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Finally, 22 articles met the inclusion criteria of this review (Figure 1). [2][3][4][8][9][10][11][12][13][16][17][18]20,[23][24][25][27][28][29]33,37,38 The κ value for overall agreement between reviewers for the initial eligibility decision was 0.73 (95% CI, 0.61-0.85), indicating substantial agreement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 22 articles met the inclusion criteria of this review (Figure 1). [2][3][4][8][9][10][11][12][13][16][17][18]20,[23][24][25][27][28][29]33,37,38 The κ value for overall agreement between reviewers for the initial eligibility decision was 0.73 (95% CI, 0.61-0.85), indicating substantial agreement.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included were case-control, 8,27,37 case series, 2,4,[9][10][11][12][13]16,18,20,24,25,28,29,33 or cohort studies 3,17,23,38 of level 2 to 4 evidence. There were no randomized controlled trials or level 1 studies included.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Brockmeier et al [4] performed SLAP repair on Type II SLAP lesion patients with an average follow-up period of 2.7 years, and forty-one patients (87%) reported the outcome as good or excellent. Similarly, Boesmueller et al [5] found that arthroscopic SLAP repair resulted in acceptable functional outcomes, and half of the patients involved in competitive sports activity were able to return to their preinjury sports levels 6 months after surgery.…”
Section: Introductionmentioning
confidence: 88%
“…A total of 53 (85%) studies included ROM as an outcome; however, only 6 (10%) studies 12,17,18,31,60,72 described a standardized method of measuring ROM. We found that 4 studies 12,17,18,60 measured ROM as part of the Constant-Murley score, detailing plane of measurement, measurement tool, and position of participant during testing. Meller et al 72 measured ROM according to the principles of the American Shoulder and Elbow Surgeons.…”
Section: Range Of Motionmentioning
confidence: 99%